Exploring User Behavior in Email Re-Finding Tasks - Mackenzie, Joel; Gupta, Kshitiz; Qiao, Fang; Awadallah, Ahmed; Shokouhi, Milad (The 28th International Web Conference (WWW 2019), 2019)
Email continues to be one of the most commonly used forms of online communication. As inboxes grow larger, users rely more heavily on email search to effectively find what they are looking for. However, previous studies on email have been exclusive to enterprises with access to large user logs, or limited to small-scale qualitative surveys and analyses on outdated public datasets such as Enron and Avocado. In this work, we propose a novel framework that allows for experimentation with real email data. In particular, our approach provides a realistic way of simulating email re-finding tasks in a crowdsourcing environment using the workers’ personal email data. We use our approach to experiment with various ranking functions and quality degradation to measure how users behave under different conditions, and conduct analysis across various email types and attributes. Our results show that user behavior can be significantly impacted as a result of the quality of the search ranker, but only when differences in quality are very pronounced. Our analysis confirms that time-based ranking begins to fail as email age increases, suggesting that hybrid approaches may help bridge the gap between relevance-based rankers and the traditional time-based ranking approach. Finally, we also found that users typically reformulate search queries by either entirely re-writing the query, or simply appending terms to the query, which may have implications for email query suggestion facilities.